1984
DOI: 10.1039/dt9840002281
|View full text |Cite
|
Sign up to set email alerts
|

Dinucleating macrocyclic Schiff bases derived from thiophene and their metal complexes: the crystal structures of a free macrocycle and of a disilver complex

Abstract: Dinucleating macrocyclic Schiff bases derived from the condensation of thiophene-2,5-dicarbaldehyde and a number of a,o-alkanediamines are reported together with their barium and silver complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Synthesis. Heteroaromatic polyazamacrocycles containing pyridine, pyrrole, furan, and thiophene rings have been obtained following a two-step synthetic method that includes a first dipodal (2 + 2) condensation of α,ω-diamines with the corresponding dialdehydes, followed by hydrogenation of the Schiff base imine bonds. ,, However, several authors have pointed out that when such α,ω-diamines have additional NH or OH groups in the middle of the chain, the first condensation step affords a mixture of two isomers. Thus, Fenton and co-workers reported that, in the absence of metal ions, the condensation of 2,5-thiophenedicarbaldehyde with diethylenetriamine affords a solid product whose 1 H NMR spectrum corresponds to a mixture of the desired tetraimine Schiff base together with an imidazolidine isomer formed by nucleophilic addition of the two secondary amine groups of the tetraimine macrocycle across the adjacent imine bonds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis. Heteroaromatic polyazamacrocycles containing pyridine, pyrrole, furan, and thiophene rings have been obtained following a two-step synthetic method that includes a first dipodal (2 + 2) condensation of α,ω-diamines with the corresponding dialdehydes, followed by hydrogenation of the Schiff base imine bonds. ,, However, several authors have pointed out that when such α,ω-diamines have additional NH or OH groups in the middle of the chain, the first condensation step affords a mixture of two isomers. Thus, Fenton and co-workers reported that, in the absence of metal ions, the condensation of 2,5-thiophenedicarbaldehyde with diethylenetriamine affords a solid product whose 1 H NMR spectrum corresponds to a mixture of the desired tetraimine Schiff base together with an imidazolidine isomer formed by nucleophilic addition of the two secondary amine groups of the tetraimine macrocycle across the adjacent imine bonds …”
Section: Resultsmentioning
confidence: 99%
“…Although several groups have detected the formation of imidazolidine derivatives related to IV in equilibrium with Schiff bases similar to III (X = NH), as far as we know there are few examples including X-ray structures , and a detailed NMR characterization of such compounds has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic ligand was synthesized by the high dilution one-to-one [2:2] condensation of diamino compound with dicarbonyl compound in ethanol. The synthesis of macrocyclic Schiff bases using metal-free condensations of primary or diamines with dialdehydes were first published by Tasker et al [52] and Fenton et al [53]. This method has also been studied in literature .…”
Section: J Heterocyclic Chem 43 1679 (2006)mentioning
confidence: 97%
“…By the inclusion of various heteroatoms, among them those forming part of heterocyclic fragments, in the chelate unit it is possible to vary the electronic and steric characteristics of the complexes precisely [4,5].In this work a path to the construction of new podands based on heterocyclic dialdehydes 2 and diethyl 2-[(2-aminophenyl)aminomethylidene]malonate (1) is presented. 2,5-Thiophenedicarbaldehyde (2a) and 2,6-pyridinedicarbaldehyde (2b) were used as heterocyclic dialdehydes.…”
mentioning
confidence: 98%
“…By the inclusion of various heteroatoms, among them those forming part of heterocyclic fragments, in the chelate unit it is possible to vary the electronic and steric characteristics of the complexes precisely [4,5].…”
mentioning
confidence: 99%